2012
DOI: 10.1037/a0027347
|View full text |Cite
|
Sign up to set email alerts
|

Validity of DSM-IV attention deficit/hyperactivity disorder symptom dimensions and subtypes.

Abstract: DSM-IV criteria for ADHD specify two dimensions of inattention and hyperactivity-impulsivity symptoms that are used to define three nominal subtypes: predominantly hyperactive-impulsive type (ADHD-H), predominantly inattentive type (ADHD-I), and combined type (ADHD-C). To aid decision-making for DSM-5 and other future diagnostic systems, a comprehensive literature review and meta-analysis of 546 studies was completed to evaluate the validity of the DSM-IV model of ADHD. Results indicated that DSM-IV criteria i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

78
684
6
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 724 publications
(796 citation statements)
references
References 78 publications
(123 reference statements)
78
684
6
12
Order By: Relevance
“…This is in keeping with research suggesting that reported ADHD symptom levels and ADHD subgroup membership (i.e. inattentive, hyperactive‐impulsive) can fluctuate over time (Willcutt et al., 2012). Moffitt et al.…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with research suggesting that reported ADHD symptom levels and ADHD subgroup membership (i.e. inattentive, hyperactive‐impulsive) can fluctuate over time (Willcutt et al., 2012). Moffitt et al.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical diagnostic decisions are based on the assumptions that symptoms and impairment are related but separate constructs (10,38), and impairment could be regarded as an independent external validation of a disorder and as being essential to avoid tautology in which the same measures are used to define and externally validate a disorder (8). However, when the same rater evaluates both symptoms and impairment, this does not necessarily hold true, because rater bias may be a problem.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In addition, the predictive validity of ADHD, ODD, and CD symptoms has been found to be only moderate for 4-year-old preschool children (8,32,53), and no studies have tested the predictive validity of CD symptoms for children less than 4.5 years old. Thus, our knowledge of the developmental trajectories of CD symptoms is still limited.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The validity of the bidimensional structure of the AttentionDeficit and Hyperactivity Disorder (ADHD) -defined by the "inattention" and "hyperactivity/impulsivity" dimensions -holds a broad empirical support (Willcutt et al, 2012). Nevertheless, the clinical heterogeneity of ADHD is patent in many different levels (Wåhlstedt, Thorell, & Bohlin, 2009), most notably at neuropsychological level (Coghill, Seth, & Matthews, 2014;Sjöwall, Backman, & Thorell, 2015;van Hulst, de Zeeuw, & Durston, 2015).…”
Section: Introductionmentioning
confidence: 99%